Do Clinical Parameters Predict First Planned Extubation Outcome in the Pediatric Intensive Care Unit?. (February 2015) - Laham, James L.; Breheny, Patrick J.; Rush, Amanda
Context: There is absence of evidence-based guidelines to determine extubation readiness in the pediatric intensive care unit (PICU). Objective: Evaluate our practice of determining extubation readiness based on physician judgment of preextubation ventilator settings, blood gas analysis, and other factors potentially affecting extubation outcome. Design: Prospective cohort study from August 2010 to April 2012. Setting: Academic, multidisciplinary PICU. Patients: A total of 319 PICU patients undergoing first planned extubation attempt. Interventions: None. Measurements: Determine the extubation success rate and evaluate factors potentially affecting extubation outcome. The PICU length of stay (LOS) and cost were also recorded. Subgroup analysis was performed based on days of mechanical ventilation (MV). Results: A total of 319 consecutive patients underwent first planned extubation attempt with a 91% success rate. Factors associated with extubation failure were the length of MV ( P < .0001, odds ratio [OR] 2.20); age ( P = .02, OR 0.54); preextubation steroids ( P = .04, OR 2.40); and postextubation stridor ( P < .01, OR 3.40). Ventilator settings and blood gas results had no association with extubation outcome with 1 exception, ventilator rates ≤ 8 were associated with extubation failure in patients with ≤1 day of MV. Extubation failure was associated with prolonged PICU LOS and excess cost, with failures staying 14 days longer ( P < .0001) and costing 3.2 time more ( P < .0001) than successes. Conclusions: Physician judgment to determine extubation readiness led to a first planned extubation success rate of 91%. Age and the length of MV were primary risk factors for failed extubation. In patients with ≤1 day of MV, our findings suggest that confidence in extubation readiness following weaning to low ventilator rates may not be justified. Furthermore, reliance on preextubation ventilator settings and blood gas results to determine extubation readiness may lead to unnecessary prolongation of MV, thereby increasing the PICU LOS and excess cost. These findings are hypothesis generating and require further study for confirmation.